2002
DOI: 10.1007/s00464-001-9194-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic CO2-insufflation on Tumor-associated molecules in cultured colorectal cancer cells

Abstract: The present study demonstrates CO2-insufflation to influence the expression of E-cadherin, I-CAM1 and CD44. Whether these changes increases the metastatic potential of colorectal cancer cells in vivo needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This finding suggests that our laparoscopic procedure for D2 lymphadenectomy was sufficient for locally advanced cancer. On the other hand, regarding the recurrence pattern, in vivo studies have shown that laparoscopy with CO 2 insufflation might stimulate the growth of dormant tumor cells into overt liver metastases [34,35]. The pattern in our study might be consistent with the theory that laparoscopy with CO 2 insufflation might trigger the growth of dormant tumor cells into overt liver metastases, however, further experimental studies and clinical data collection are necessary to confirm the different recurrence pattern for LAG.…”
Section: Discussionsupporting
confidence: 84%
“…This finding suggests that our laparoscopic procedure for D2 lymphadenectomy was sufficient for locally advanced cancer. On the other hand, regarding the recurrence pattern, in vivo studies have shown that laparoscopy with CO 2 insufflation might stimulate the growth of dormant tumor cells into overt liver metastases [34,35]. The pattern in our study might be consistent with the theory that laparoscopy with CO 2 insufflation might trigger the growth of dormant tumor cells into overt liver metastases, however, further experimental studies and clinical data collection are necessary to confirm the different recurrence pattern for LAG.…”
Section: Discussionsupporting
confidence: 84%
“…These results suggest that our procedure for lymphadenectomy was sufficient for T2b cancer. On the other hand, regarding the recurrence pattern, several in vivo studies have shown laparoscopy with carbon dioxide insufflations seemed to stimulate the growth of dormant tumor cells into overt liver metastases [24,25]. However, further experimental studies and clinical data collection are necessary to confirm the different recurrence pattern between the two groups.…”
Section: Journal Of Surgical Oncologymentioning
confidence: 95%
“…The design of the experiments, with placement of HA membrane on non-traumatized peritoneum, additionally allowed to study this. The effect of HA itself seems dualistic based on its interactions with the surface receptor CD44, which is present on a variety [20,21]. Zeng et al [22] demonstrated that tumour growth can be inhibited in vivo by HA oligomers, probably due to an effect on the interaction of endogenous HA and CD44.…”
Section: Discussionmentioning
confidence: 99%